비정질 합금의 자유부피 생성기구: 분자동력학적 고찰 - 이창면; Chang Myeon Lee; 박경원; Kyoung Won Park; 이병주; Byeong Joo Lee; 심재혁; Jae Hyeok Shim; 이재훈; Jae Hoon Lee; 이재철; Jae Chul Lee (대한금속·재료학회지, 46(11), 2008)
This study examined the creation mechanism of free volume during homogeneous deformation induced by the elastostatic compression at room temperature. Experiments demonstrated that amorphous alloys subjected to the elastostatic compression underwent structural disordering, during which densely packed polyhedra breakdown to form new, loosely packed ones, resulting in the creation of excess free volume. A combination of experiments and molecular dynamics simulations are used to explore fundamental issues on how free volume is created during elastostatic compression.